Apropriação de práticas de numeramento em um contexto de formação de educadores indígenas - Ruana Priscila da Silva (2012)
This project analyzes the ways in which educators in training indigenous, ethnic Pataxó Training Course Intercultural Indigenous Educators (FIEI/REUNI) qualification in Mathematics, Faculty of Education, Federal University of Minas Gerais is appropriated practices (discursive) of school numeracy. The empirical data analyzed here consists of narratives and transcripts of interactions among students, teachers, students and trainers during various stages of training course, games in which we could identify different discursive modes of appropriation. Operationalize our analysis by reference to the concepts of numeracy practices, appropriation and contributions from an ethnomathematics approach, since our thinking about the positions taken by students in relation to indigenous ownership practices (discursive) of numeracy, as well as in relation to numeracy practices forged in the context of school education, at all times considered the socio-cultural dimension of such practices. Our analysis also highlighted various tensions: those that are engendered in the composition of a curriculum of Indigenous Education in the confrontation between, on one hand, demands and discourses that propose a project based on different traditions and experiences of the village and on the other hand, the strength of the structure of the school system; tensions that are established in the processes of appropriation of practices (discursive) of numeracy education experienced by Indian students who are struggling in the prospect of a more mathematical "school" and the mobilization of an indigenous tradition of mathematical knowledge , and tensions generated by the silence imposed by the school context to everyday practices of students and students of the course FIEI/REUNI-Mathematics, as well as the tactics they developed to familiarize students with the knowledge and permeate them with their livelihoods. Therefore, our study sought to identify, in particular, values, strategies and knowledge mobilized by these Indian students to take ownership of these social practices and to include as subjects of knowledge and culture in this area of human communication shaped by School Education.